Who came first, Ezra or Nehemiah? The synchronistic approach - Demsky, Aaron 1938- (1994)
One of the most difficult and intriguing historical problems of the Period of the Restoration is the relative and absolute chronologies of Ezra and Nehemiah. Three basic solutions to the problem have been suggested, each with an almost equal number of adherents. Each approach has tried to come to grips with the chronological data presented in the Books of Ezra and Nehemiah. The data are sometimes so exact as to give day, month and year of a described event. Even so, these divergent opinions have raised more questions than they have answered. In this paper, we review the basic assumptions and present a new reconstruction which we call the "Synchronistic Approach". We submit that the two historiographic strands, i.e., the "Ezra Source" and the "Nehemiah Memoir" are based on two different, overlapping dating systems: a priestly and civil chronology, respectively. This enables us to account for all the dated events in the books and to conclude that Nehemiah arrived in Jerusalem in the spring of 445 BCE and Ezra in the summer of 443 BCE.
Keywords: Esra -- Biblische Person; Nehemia -- Biblische Person; Bibel